PENGEMBANGAN LEMBAR KEGIATAN SISWA (LKS) MODEL LEARNING CYCLE 5E - Muhamad Zikrullah; Wildan -; Yayuk Andayani (Jurnal Penelitian Pendidikan IPA, 2016)
The aims of this study were to generate 5E learning cycle model student’s work sheet wich suitable to be implemented on subject matter of the reduce-oxidace rections at class X. The method used in this study was according to the model of 4D development were Define, Design, Develop, and Disseminate. The results of limited testing by 6 students and 2 teacher’s chemistry of MAN 1 Mataram and results of the expert validation by 3 validators showed that 5E learning cycle model student’s work sheet was very suitable to be used with scores 3,36, 3,37, dan 3,33 on scale 1-4Keywords: Student’s Work Sheet, 5E Learning Cycle Model